Long non‐coding RNA: A new paradigm for lung cancer. Issue 11 (31st August 2015) - Khandelwal, Akanksha; Bacolla, Albino; Vasquez, Karen M; Jain, Aklank
<x xml:space="preserve">Abstract</x> Lung cancer is the leading cause of cancer‐related deaths worldwide. Recent advances in whole genome transcriptome analysis have enabled the identification of numerous members of a novel class of non‐coding RNAs, i.e., long non‐coding RNAs (lncRNAs), which play important roles in a wide range of biological processes and whose deregulation causes human disease, including cancer. Herein we provide a comprehensive survey of lncRNAs associated with lung cancer, with particular focus on the functions that either facilitate or inhibit the progression of lung cancer and the pathways involved. Emerging data on the use of lncRNAs as biomarkers for the diagnosis and prognosis of cancer are also discussed. We cast this information within the wider perspective of lncRNA biogenesis and molecular functions in the cell. Relationships that exist between lncRNAs, genome‐wide transcription, and lung cancer are discussed. Deepening our understanding on these processes is critical not only from a mechanistic standpoint, but also for the development of novel biomarkers and effective therapeutic targets for cancer patients. © 2015 Wiley Periodicals, Inc.